2022
DOI: 10.21203/rs.3.rs-1799902/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biomimetic Cultivation of Atrial Tissue Slices: a Novel Platform for In-Vitro Atrial Arrhythmia Studies

Abstract: Living myocardial slices (LMS) are beating sections of intact human myocardium that maintain 3D microarchitecture and multicellularity, thereby overcoming most limitations of conventional myocardial cell cultures. We introduce a novel method to produce LMS from human atria and apply pacing modalities to bridge the gap between in-vitro and in-vivo atrial arrhythmia studies. Human atrial biopsies from 14 patients undergoing cardiac surgery were dissected to tissue blocks of ~ 1 cm2 and cut to 300 µm thin LMS wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The vibratome then produces slices with a thickness of 150-400 µm coming from different layers within the myocardium. In general, vibratome speed should be lowered for atrial tissues in comparison with ventricular tissues, as atrial tissue is more fragile and therefore at higher risk for rupturing on the vibratome (Kang et al, 2016;Amesz et al, 2022). In addition, slices infiltrated with large amounts of fibrous and adipose tissue often show separation of myocardial bundles and are therefore not routinely selected for culture.…”
Section: Lms Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…The vibratome then produces slices with a thickness of 150-400 µm coming from different layers within the myocardium. In general, vibratome speed should be lowered for atrial tissues in comparison with ventricular tissues, as atrial tissue is more fragile and therefore at higher risk for rupturing on the vibratome (Kang et al, 2016;Amesz et al, 2022). In addition, slices infiltrated with large amounts of fibrous and adipose tissue often show separation of myocardial bundles and are therefore not routinely selected for culture.…”
Section: Lms Techniquementioning
confidence: 99%
“…Hence, cardiomyocytes in LMS are wellaligned in a striated fashion and linked by gap junctions, and membrane bound connexins are preserved (Habeler et al, 2009). To date, LMS have been predominantly produced from ventricular specimens, but can also be produced from atrial tissue (Girmatsion et al, 2009;Biliczki et al, 2019;Amesz et al, 2022). In addition, Kang et al (2016) produced slices from the sinoatrial node region and observed automaticity in these LMS.…”
Section: Electrophysiological Modelmentioning
confidence: 99%
See 2 more Smart Citations